Ex-situ liver surgery without veno-venous bypass - Zhang, Ke-Ming (World journal of gastroenterology : WJG, 2012)
AIM：To evaluate the results of hepatic resection with ex-situ hypothermic perfusion and without veno-venous bypass.METHODS：In 3 patients with liver tumor,the degree of the inferior vena cava and/or main hepatic vein involvement was verified when the liver was dissociated in the operation.It was impossible to resect the tumors by the routine hepatectomy,so the patients underwent ex-situ liver surgery,vein cava replacement and hepatic autotransplantation without veno-venous bypass.All surgical procedures were carried out or supervised by a senior surgeon.A retrospective analysis was performed for the prospectively collected data from patients with liver tumor undergoing ex-situ liver surgery,vein cava replacement and hepatic autotransplantation without veno-venous bypass.We also compared our data with the 9 cases of Pichlmayr＇s group.RESULTS：Three patients with liver tumor were analysed.The first case was a 60-year-old female with a huge haemangioma located in S1,S4,S5,S6,S7 and S8 of liver;the second was a 64-year-old man with cholangiocarcinoma in S1,S2,S3 and S4 and the third one was a 55-year-old man with a huge cholangiocarcinoma in S1,S5,S7 and S8.The operation time for the three patients were 6.6,6.4 and 7.3 h,respectively.The anhepatic phases were 3.8,2.8 and 4.0 h.The volume of blood loss during operation were 1200,3100,2000 mL in the three patients,respectively.The survival periods without recurrence were 22 and 17 mo in the first two cases.As for the third case complicated with postoperative hepatic vein outflow obstruction,emergency hepatic vein outflow extending operation and assistant living donor liver transplantation were performed the next day,and finally died of liver and renal failure on the third day.Operation time（6.7 ± 0.47 h vs 13.7 ± 2.6 h） and anhepatic phase（3.5 ± 0.64 h vs 5.7 ± 1.7 h） were compared between Pichlmayr＇s group and our series（P = 0.78）.CONCLUSION：Ex-situ liver resection and liver autotransplantation has shown a potential for treatment of complicated hepatic neoplasms that are unresectable by traditional procedures.